Monitoring of Unfractionated Heparin in Severe COVID-19: An Observational Study of Patients on CRRT and ECMO - Alexander S. Streng; Thijs Delnoij; Mark M. G. Mulder; Jan Willem Sels; Rick J. H. Wetzels; Paul Verhezen; Renske H. Olie; Jeroen P. Kooman; Sander M. J. van Kuijk; Lloyd Brandts; Hugo Ten Cate; Roberto Lorusso; et al. (2020)
Abstract Objective Severe cases of coronavirus disease 2019 (COVID-19) can require continuous renal replacement therapy (CRRT) and/or extracorporeal membrane oxygenation (ECMO). Unfractionated heparin (UFH) to prevent circuit clotting is mandatory but monitoring is complicated by (pseudo)-heparin resistance. In this observational study, we compared two different activated partial thromboplastin time (aPTT) assays and a chromogenic anti-Xa assay in COVID-19 patients on CRRT or ECMO in relation to their UFH dosages and acute phase reactants. Materials and Methods The aPTT (optical [aPTT-CS] and/or mechanical [aPTT-STA] clot detection methods were used), anti-Xa, factor VIII (FVIII), antithrombin III (ATIII), and fibrinogen were measured in 342 samples from 7 COVID-19 patients on CRRT or ECMO during their UFH treatment. Dosage of UFH was primarily based on the aPTT-CS with a heparin therapeutic range (HTR) of 50–80s. Associations between different variables were made using linear regression and Bland–Altman analysis. Results Dosage of UFH was above 35,000IU/24 hours in all patients. aPTT-CS and aPTT-STA were predominantly within the HTR. Anti-Xa was predominantly above the HTR (0.3–0.7 IU/mL) and ATIII concentration was >70% for all patients; mean FVIII and fibrinogen were 606% and 7.5 g/L, respectively. aPTT-CS correlated with aPTT-STA (r 2 = 0.68) with a bias of 39.3%. Correlation between aPTT and anti-Xa was better for aPTT-CS (0.78 ≤ r 2 ≤ 0.94) than for aPTT-STA (0.34 ≤ r 2 ≤ 0.81). There was no general correlation between the aPTT-CS and ATIII, FVIII, fibrinogen, thrombocytes, C-reactive protein, or ferritin. Conclusion All included COVID-19 patients on CRRT or ECMO conformed to the definition of heparin resistance. A patient-specific association was found between aPTT and anti-Xa. This association could not be explained by FVIII or fibrinogen.